(SiC/AlN)2 multilayer film as an effective protective coating for sintered NdFeB by magnetron sputtering. (18th August 2017) - You, Yu; Li, Heqin; Huang, Yiqin; Tang, Qiong; Zhang, Jing; Xu, Jun
Abstract: SiC/AlN and (SiC/AlN)2 multilayer films with a well-arranged bilayer structure and a four-layer structure are prepared respectively on NdFeB substrates by a magnetron sputtering method. Crystal phase and microstructures of the SiC/AlN and (SiC/AlN)2 films are investigated using x-ray diffraction (XRD), field-emission scanning electron microscope (FESEM) and atomic force microscope (AFM). It is observed that the surface of the (SiC/AlN)2 four-layer film is much denser and smoother than that of the SiC/AlN bilayer film. Corrosion behaviors of the NdFeB substrates coated with SiC/AlN and (SiC/AlN)2 films as well as the bare NdFeB substrate are evaluated by potentiodynamic polarization curve tests. It is revealed that the lateral growth structures developed in interfaces are favorable for an enhanced corrosion resistance. Corrosion current densities of the (SiC/AlN)2 coated NdFeB measured in acid, alkali and salt solutions are 2.796 × 10 −9, 3.65 × 10 −6, and 2.912 × 10 −6 A cm −2, respectively, which are much lower than those of the bare NdFeB and the SiC/AlN coated NdFeB.